Vital Links: Roads and Light Railways in the Military Operations of the Canadian Corps during the First World War - Shoebottom, Bradley (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2023)
During the Hundred Days Offensive of the First World War, the Canadian Corps on the Western Front played a significant role in British operations that far outweighed its modest size of 100,00 troops. The Canadian Corps successfully took all its objectives in the last hundred days, in part because it had a well-evolved engineer and mobility support function operating over a multi-modal transportation network. This network consisted of a group of nonhuman actors made-up of road and light railway using a combination of horse transport, motor lorries, supply tanks, and tramways backed by a robust group of human actors in the form of engineers and army service corps to ensure the supplies moved forward.